Additionality and charitable support for public services: community fundraiser perspectives in a tax-funded national health service - Steph Haydon; Ellen Stewart; Francesca Vaghi (Voluntary Sector Review, 2026)
Additionality refers to the idea that charitable contributions to publicly-funded services should enhance, not replace, state provision. While it is often assumed that donors will avoid substitution of public funding when seeking causes to support, longstanding traditions of charitable support for public services (for example schools, healthcare facilities) endure. Through four case studies of charitable activities supporting NHS hospitals in the United Kingdom, we examine the perspectives of community fundraisers and the staff who work with them. Professional fundraisers often described a tension between selling their cause while conveying its additionality. Meanwhile, many community fundraisers were initially drawn to support healthcare services to address identified shortfalls in provision. Once involved in fundraising efforts, participants often develop a deeper commitment to the social experience of taking part. This generates ongoing engagement that largely overrides additionality concerns, and that limits the potential for fundraising to be redirected to alternative causes.